East Asian welfare regimes in transition : from Confucianism to globalisation - Walker, Alan, 1952 October 13-; Wong, Chack-kie (Policy Press, 2005)
This book puts the spotlight on the Chinese and South-East Asian welfare systems, providing an up-to-date assessment of their character and development. In particular it examines the underlying assumptions of these systems and how the processes of globalisation are impacting on them. As well as specific country case studies, there is a valuable comparative analysis of Eastern and Western welfare states.